Healthcare Workers' Safety; A Necessity for a Robust Health System - Kengo Nathan Ezie; Felix Amekpor; Godfred Yawson Scott; Angyiba Serge Andigema; Shuaibu Saidu Musa; Berjo Dongmo Takoutsing; Don Eliseo Lucero-Prisno III (Ubiquity Press, 2023)
It is a prevalent misconception that healthcare professionals are specialists and thus can effectively manage their health. This is probably true, but given recent pandemics and the rise in violence in medical settings, one is compelled to question whether their health and safety are sufficient for a robust healthcare system. This is important because protecting and promoting the health, safety, and well-being of health workers will improve the quality of patient care and increase the resilience of health services in the face of outbreaks and public health emergencies. We thus strive to answer this question and suggest potential remedies to this growing public health issue.